Assessing the expansion and success of a restored population of Gongolaria barbata (Stackhouse) Kuntze (Fucales, Phaeophyceae) using high-precision positioning tools and size distribution frequencies - ALICIA GRAN; JUANCHO MOVILLA; ENRIC BALLESTEROS; MARTA SALES; IGNACIO BOLADO; CRISTINA GALOBART; MARIA ELENA CEFALÌ (Mediterranean Marine Science, 2022)
Ongoing human pressures over recent decades have caused the loss and ensuing impoverishment of the complexity and diversity of Mediterranean habitats dominated by algal species of the order Fucales. Gongolaria barbata, a habitat-forming Fucales species that has disappeared in several places across the Mediterranean, was reintroduced in a cove (Cala Teulera, Maó Bay, Menorca) where it was known to have been locally extinct for more than 40 years. Reintroduction was performed in 2011 using innovative non-destructive techniques. Here we describe the expansion patterns of the population ten years after its reintroduction, and we look at the size-structure distribution of the restored population compared to one of the only natural populations known in Spain (Fornells Bay, Menorca). Newly settled individuals exhibit a progressive dispersal pattern from restoration sites, favouring rocky substrates at the shallowest level parallel to the shore. The area occupied by G. barbata has increased by almost three orders of magnitude in ten years, from approximately 3.6 m2 of the initially restored area to a current restored area of 2093 m2. Recruits and juveniles dominate the restored population but some individuals have reached large size classes, the overall size distribution resembling the reference population. The high-resolution cartography included in our study enables an accurate mid to long-term assessment of the expansion of G. barbata. Incorporating such tools in restored marine forests would facilitate the implementation of efficient management policies that will help reinforce their conservation

Genetic and Morphological Evidence to Split the Coris julis Species Complex (Teleostei: Labridae) Into Two Sibling Species: Resurrection of Coris melanura (Lowe, 1839) Redescription of Coris julis (Linnaeus, 1758) - Sergio Ramírez-Amaro; Francesc Ordines; Ronald Fricke; Ignacio Ruiz-Jarabo; Ignacio Bolado; Enric Massutí (Frontiers in Marine Science, 2021)
The genus Coris contains 28 valid species, most of them with an Indo-Pacific distribution and only two species recognized from the eastern Atlantic: Coris atlantica and C. julis . This last species has a large variability in its coloration, which caused that during the first half of XIX century the sexes were considered as different species. Two liveries have been described for C. julis : (i) primary or “ giofredi ,” which corresponds to females and primary-phase males and is considered common for Atlantic and Mediterranean populations; and (ii) the secondary or “ julis ” which corresponds to secondary-phase males, which is different for Atlantic and Mediterranean populations. In this study we demonstrate the existence of two sibling species within the C. julis species complex. Morphological and molecular analyses showed that this species complex is composed of two species: (i) C. julis , distributed mainly in the Mediterranean, from which the species was originally described; and (ii) C . melanura , a species described by Lowe in 1839 which is resurrected here, mainly distributed in the eastern Atlantic and western Mediterranean. We also discuss the possible speciation event to understand the contemporary distribution patterns of Coris species in the eastern Atlantic and Mediterranean.